2010
DOI: 10.1097/cmr.0b013e3283390365
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of bevacizumab with dacarbazine and daily low-dose interferon-α2a as first line treatment in metastatic melanoma

Abstract: Metastatic melanomas are hypervascular tumours with poor prognosis. We hypothesized that treatment of metastatic melanoma with a combination of bevacizumab, a monoclonal antibody against vascular endothelial growth factor, dacarbazine (DTIC) and low-dose interferon alpha-2a (IFN-alpha2a) might lead to a synergistic inhibition of angiogenesis and regression of tumours. Patients with metastatic melanoma were treated with bevacizumab (5 mg/kg every 2 weeks), DTIC (200 mg/m days 1-5 every 4 weeks) and IFN-alpha2a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Because it remodels the extracellular .4cta Derm Ï enereot 93 matrix and promotes the sprouting and growth of new blood vessels by making vascular endothelial growth factor (VEGF) available to the VEGFR-2/flk receptor on endothelial cells, MMP-9 is a linchpin in tumour progression (29). Actually, several reports revealed that the expression of MMP-9 on tumours was correlated with the progression or prognosis of several skin tumours, such as malignant melanoma, SCC, basal cell carcinoma, mycosis fungoides, extrammamary Paget's disease and angiosarcoma (20,(29)(30)(31)(32)(33)(34). In addition, other reports indicate that the expression of MMP-9 on immunosuppressive macrophages in the tumour microenvironment contributes to tumour invasion and metastasis (10,11,20,34,35).…”
Section: Discussionmentioning
confidence: 98%
“…Because it remodels the extracellular .4cta Derm Ï enereot 93 matrix and promotes the sprouting and growth of new blood vessels by making vascular endothelial growth factor (VEGF) available to the VEGFR-2/flk receptor on endothelial cells, MMP-9 is a linchpin in tumour progression (29). Actually, several reports revealed that the expression of MMP-9 on tumours was correlated with the progression or prognosis of several skin tumours, such as malignant melanoma, SCC, basal cell carcinoma, mycosis fungoides, extrammamary Paget's disease and angiosarcoma (20,(29)(30)(31)(32)(33)(34). In addition, other reports indicate that the expression of MMP-9 on immunosuppressive macrophages in the tumour microenvironment contributes to tumour invasion and metastasis (10,11,20,34,35).…”
Section: Discussionmentioning
confidence: 98%
“…If there was no progression after six cycles, the treatment was continued with maintenance therapy with bevacizumab (5 mg/kg) on days 1 and 15 with or without continuous IFN-a2a 3 million international units subcutaneously daily. The treatment schedule has been published in detail recently ( [20]; ML 18580/www. clinicaltrials.gov).…”
Section: Bevacizumab-dacarbazine-interferon Trialmentioning
confidence: 99%
“…Eligibility criteria also included the following: age greater than or equal to 18 years, life expectancy greater than or equal to 3 months, Eastern Cooperative Oncology Group performance status less than or equal to 2, normal organ and bone marrow function, no previous treatment for metastatic disease [bevacizumab-dacarbazine (DTIC)-interferon-a2a (IFN-a2a) trial] or progressing melanoma irrespective of previous treatments [carboplatin, vinorelbine, and subcutaneous interleukin-2 (IL-2) trial], and no central nervous system metastases. The study protocols were approved by the local ethics committees and each patient provided a written informed consent to participate in the trials [20,21]. The key clinical characteristics of the patients are shown in Table 1.…”
Section: Patient Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab is a monoclonal antibody that can selectively bind VEGF and block its binding with receptors. It has been widely applied in the treatment of metastatic melanoma (182)(183)(184)(185). In a randomized, double-blind phase II study (BEAM study), 214 metastatic melanoma patients were randomized into carboplatin + paclitaxel + bevacizumab (CPB) group or placebo group (CP) at a proportion of 2:1.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%